REVIEW FOOD ENGINEERING HEALTHY FOOD Centella asiatica TO PREVENT STUNTING IN TODDLERS - Annisa Ridlayanti; Yuliani, Anita; Masdinarsyah, Imas; Suryadi, Astuti; Stefany T, Gabriel; Asqalani, M Syakieb (Indonesian Midwifery and Health Sciences Journal, 2025)
Background: WHO ranked Indonesia as the third country with the highest prevalence of stunting in Asia. In Indonesia, 1 in 3 children under five is potentially stunted (26.6%) (Prendergast & Humphrey, 2014). Stunting is a chronic nutritional problem caused by a long lack of nutritional intake. (Eka Kusuma & Nuryanto, 2013). In Indonesia, Centella is easy to get because it grows in the tropics. Benefits of Centella in addition to being a source of vegetable protein as well as antioxidants, anti-inflammatory, nerve protectors, strengthening the brain nerves, making concentration and memory higher, and can prevent stunting. Preliminary studies show that 8 out of 10 children like processed healthy foods in the form of brownies, nuggets, crackers, and seaweed candies that Centella has added. Accounting nutritional facts from the healthy food Centella is the purpose study. Method: This research is an advanced study of exploratory study with a pre-experimental approach model one shoot case study. At this stage, this study used a laboratory test in the form of nutritional facts tests. Some of these tests will be conducted at the food engineering laboratory of Pasundan University Bandung. Result: The results show that the nutritional content in 1 cupcake brownie with 5 variants of toppings (choco chips, almonds, cheese, nuts, white chips) shows the content of Kkal/ 100 grams range from 319.97-322.44 Kcal, and the percentage of Calories Nutritional Rate Adequacy is 100 grams range from 16.00 - 16.19%. Conclusion : Therefore, Centella’s innovation as a healthy snack to overcome stunting growth in toddlers can be developed as a healthy natural product as one of the characteristics of Indonesian food.